Sex differences in morphological dimensions in twelve-year-old children from Imotska Krajina - Gudelj Ceković, Ines (Array, 2009)
Abstract: The aim of the study was to identify and compare morphological characteristics of 12-year-old male and female children from Imotska krajina. The structure of a set of 23 morphological space variables were determined in a sample of 75 male and 67 female children by use of factor analysis for each sex in separate. Factor structure showed two basic superior latent dimensions responsible for directly measurable manifestations of morphological parameters in both male and female children. One of these two dimensions behaved as a general mechanism of growth and development, whereas the other showed a bipolar pattern. Bipolarity was almost exclusively determined by adipose tissue on one pole, and by skeletal longitudinal growth on the opposite pole.